Features Of The Development Of Memory In Preschool Children - Mushtariy Mirzakizi Abdullayeva (Euro Asian Journal Publishing, 2024)
Memory is one of the necessary mental processes, without which a child's intellectual development is impossible. Sufficient attention should be paid to its development in preschool age. It is with the help of memory that the child acquires new knowledge, learns the world or can study at school, acquires the necessary knowledge, skills and abilities. In memory training, we teach children to memorize, store and consolidate information using simple exercises and games. The memory of preschool children is characterized by mechanical memorization without understanding the given information. The task of parents and educators is to teach the child to consciously implement new knowledge in a logical way. Voluntary memorization and repetition of information should gradually be transferred to conscious memorization. Visual memory develops up to two years. At this age, the child's nervous system is actively developing, and the volume of information increases
Keywords: memory; process; treatment; figurative